Do controle ao cybercontrole: impactos na greve e novas perspectivas de resistência - Natália das Chagas Moura (2019)
This research is about control and cybercontrol, analyzing their implications in the strike and tracing new perspectives of resistance. Control has been a hallmark throughout the history of strikes and it is justified by the potentiality and strength of collective resistance. It goes back to some historical background on the control of strikes from its origins, exposing its meanings. Other forms of control – such as judicial, police, union-employer, media, social and business control, and especially, control through disruptive technologies – are identified. Starting from the new logic of material reproduction, called “surveillance capitalism”, in which data has become the most profitable and valued commodity, as well as a source of power, it is imperative to understand the functionalities and applications of Big Data technologies, of devices of geolocation, algorithms, artificial intelligence and other advanced technological innovations, so that one can reflect and think ways of resisting the totalizing and ubiquitous cybercontrol practiced mainly by the platform-companies. Cybercontrol results from complex and permanent surveillance of a multitude of cybercontracted people and has a disastrous impact on strikes, resulting in various forms of anti-unionism. We highlight new perspectives of collective resistance, such as cyberboicot, overexposure of the brand and the image of the company, the adoption of atypical strikes, the joint and simultaneous action of the workers, cyber-resistances such as platform cooperativism, cyberactivism and the technolopolitics of resistance, protection of personal data covered by Law 13.709/2018 and the use of the constitutional action of Habeas Data. Strikes have always attracted control, and, as a result, control over strikes incites resistance. For this research, the methodology of bibliographic analysis for the investigation of books, articles, statistical, legislative and jurisprudential data was chosen. This research is justified by the need to rethink new perspectives of resistance to anti-unionism and, above all, to cybernetic control, which has even impacted the articulation and the outbreak of strikes. The strike is the seed from which germinated the Labor Law. By its very creative, inventive and constructive nature, it is necessary to defend the strike and, through it, to resist.